Farmer training on aflatoxin prevention using low-cost, locally available materials, combined with market incentives for safer food - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
A randomized controlled trial was conducted in northern Ghana over the course of two seasons to test the three interventions and results published. Results indicate that training farmers substantially improves post-harvest practices. Drying sheet distribution and to a lesser extent the premium price lead to further improvements.